KEUNIKAN SISTEM PENDIDIKAN DI CHINA - Rohimah, Siti Baitir; Alam, Abdal Malik Fajar (Jazirah: Jurnal Peradaban dan Kebudayaan, 2023)
The need to research and evaluate the characteristics of educational systems in various states arises from the contemporary internationalization of education processes. The prominence of Chinese education, as well as our strong relationship and collaborative efforts with the PRC, led us to examine the distinctive characteristics of the Chinese educational framework. Traditional cultural and spiritual norms also define the Chinese educational system and the world's most popular educational trends. Because China is experiencing tremendous economic expansion, the country need highly skilled specialists, which means high-quality and inexpensive education. This calls for reforming the current educational system. The value and status of education are growing across all demographic groups. Educational institutions carry out a wide range of educational tasks in addition to teaching youngsters. Since embracing the Soviet pedagogy system in general, the People's Republic of China (PRC) has undergone various phases of educational reform since 1978. These have included restoring the school system, elevating the status of teachers, and enhancing the standard and accessibility of education for the general public. We have examined the current Chinese educational system in this article, which consists of preschool, school, and higher education.